Ternary networks : reliability and Monte Carlo - Gertsbakh, Ilya (SpringerBriefs in Electrical and Computer Engineering, 2014)
Ternary means "based on three". This book deals with reliability investigations of  networks whose components subject to failures can be in three states -up, down and middle (mid), contrary to traditionally considered networks  having only binary (up/down) components. Extending binary case to ternary allows to consider more realistic and flexible models for communication, flow and supply networks.